Cost Reduction of Steel Strapping Buckles in Steel Coil Slitting and Packing Processes - เลิศโกวิทย์, พิพัฒน์; ทับพร, ธีระพงษ์; ทับพร, เอกพล; ตันสกุล, กวิสรา; แสงบุดดี, กิตติพงษ์; ครั่นคร้ามผิด, สุภางค์; วชิรสุรงค์, ญานพินิจ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
At present the domestic steel industry to become more competitive because the steel industry has grown greatly causing to increase the production cost. This aims to design and produce tie-down clips for internal production processes within the company replacing the need for external purchases. The study had investigated the strength of materials suitable for stamping into tie-down clips utilizing production waste to create these clips. Three types of steel will be tested: Color galvanized (CG Steel) Electro galvanizing (EG steel) and Pre galvanized (GI Steel).           From the testing of the strength of three types of materials: Color Galvanized Steel (CG Steel) Electro Galvanizing Steel (EG Steel) and Pre Galvanized Steel (GI Steel) the elongation value of Color Galvanized Steel (CG Steel) is the highest at 50.3% followed by Pre Galvanized Steel (GI Steel) at 49.5% and Electro Galvanizing Steel (EG Steel) with the lowest elongation value of 44.7%. In the comparison of costs for ordering external strap clips versus producing strap clips from waste in the company's manufacturing process the costs differ as follows: ordering external strap clips costs 0.5 baht per piece while producing clips from manufacturing waste costs 0.1475 baht per piece. This results in a cost reduction of 0.3525 baht per piece when producing strap clips from the manufacturing process.